The future of US agricultural and rural development policy: Where do the 2020 presidential candidates stand? - Smith, Vincent H.; Glauber, Joseph W. (American Enterprise Institute, 2020)
Agricultural policy issues play an outsized role in the race for the presidency if only because the primary season begins in Iowa, where corn is king, and other rural states such as New Hampshire and South Carolina. On a bipartisan basis, almost every candi-date, including President Donald Trump, supports current price and income-support policies, the federal crop insurance program, and soil and other conserva-tion initiatives that direct substantial taxpayer-funded payments to farm businesses. The major difference is that most of the Democratic candidates seek to shift such payments toward small and medium-sized farms and away from large-scale agribusiness farms. The candidates for the Democratic Party’s nom-ination do differ on agricultural trade policy. Mayor Mike Bloomberg is the only candidate whose sup-port for free trade is unequivocal. Some candidates, including former Vice President Joe Biden, Sen. Amy Klobuchar, and Sen. Elizabeth Warren, have sup-ported some trade agreements with other countries (e.g., the recent US-Mexico-Canada Agreement) but would only support further trade agreements if they imposed implausibly stringent conditions regarding environmental, worker-safety, and other regula-tions in the countries with which the agreements are signed. Sen. Bernie Sanders seems generally opposed to any trade agreements and in this area seems to have more in common with President Trump, who has been willing to arbitrarily disrupt US access to over-seas markets for agricultural products in his trade and foreign policy initiatives. Finally, initiatives to address climate change through reducing carbon emissions are a common theme among all the Democratic candidates. Several, including Biden, Sanders, and Warren, have essentially adopted the Green New Deal as their cli-mate change initiative while, somewhat inconsis-tently given ethanol’s impacts on carbon emissions, supporting the renewable fuels standards for ethanol and other biofuels. Bloomberg is a notable exception, viewing biofuels as problematic but supporting substantial reductions in the use of carbon fuel. In stark contrast, President Trump has aggressively termi-nated many of the Obama administration’s climate change initiatives and, at least ostensibly, viewed cli-mate change as of no concern for his administration.